Distinctions of preparation batch for obtaining white glass coatings - Ryzhova, O.P.; Holeus, V.I.; Kyslychna, R.I.; Nahorna, T.I.; Naumenko, S.Yu. (Наука, технології, інновації, 2018)
The influence of the sequence of introduction of raw materials into the charge on the optical indicators of titanium glass coverings is studied. A rational technological procedure for the preparation of batch has been worked out, which consists of mixing in the first stage titanium dioxide and magnesium oxide, then sodium and potassium nitrate and sodium tripolyphosphate and only then sand and all other components. Досліджено вплив послідовності введення сировини у шихту на оптичні показники титанових скляних покриттів. Розроблено раціональну технологічну процедуру виготовлення партії, яка полягає у змішуванні на першій стадії діоксиду титану та оксиду магнію, потім натрієвої та калійної селітри та триполіфосфату натрію і лише потім піску та всіх інших компонентів. Исследовано влияние последовательности ввода сырья в шихту на оптические показатели титановых стеклянных покрытий. Разработана рациональная технологическая процедура изготовления партии, которая состоит в смешивании на первой стадии диоксида титана и оксида магния, затем натриевой и калийной селитры и триполифосфата натрия и только потом песка и всех других компонентов.